Obesity and MASLD: Is weight loss the (only) key to treat metabolic liver disease? - Maximilian Huttasch; Michael Roden; S. Kahl (2024)
Metabolic dysfunction-associated steatotic liver disease (MASLD) closely associates with obesity and type 2 diabetes. Lifestyle intervention and bariatric surgery aiming at substantial weight loss are cornerstones of MASLD treatment by improving histological outcomes and reducing risks of comorbidities. Originally developed as antihyperglycemic drugs, incretin (co-)agonists and SGLT2 inhibitors also reduce steatosis and cardiorenovascular events. Certain incretin agonists effectively improve histological features of MASLD, but not fibrosis. Of note, beneficial effects on MASLD may not necessarily require weight loss. Despite moderate weight gain, one PPARγ agonist improved adipose tissue and MASLD with certain benefit on fibrosis in post-hoc analyses. Likewise, the first THRβ-agonist was recently provisionally approved because of significant improvements of MASLD and fibrosis. We here discuss liver-related and metabolic effects induced by different MASLD treatments and their association with weight loss. Therefore, we compare results from clinical trials on drugs acting via weight loss (incretin (co)agonists, SGLT2 inhibitors) with those exerting no weight loss (pioglitazone; resmetirom). Furthermore, other drugs in development directly targeting hepatic lipid metabolism (lipogenesis inhibitors, FGF21 analogs) are addressed. Although THRβ-agonism may effectively improve hepatic outcomes, MASLD treatment concepts should consider all cardiometabolic risk factors for effective reduction of morbidity and mortality in the affected people.